The 12th Interntional Sago Symposium in Rikkyo University,Tokyo, Japan - Chan, Margaret Kit Yok (UiTM Sarawak, 2016)
The 12th Interntional Sago Symposium was held in Rikkyo University at Nishiikebukuro, Toshima-ku, Tokyo in Japan with the theme "The Sago Supports Human and Planet Welfare". Sponsored by the Sarwak Convention Bureau, the main task was to launch the 1 3 International Sago Symposium to be organized by Universiti Teknologi MARA in Kuching, Sarawak in September 2017. This was successfully conducted by Prof. Dato Dr. Jamil Hamali, the Rector of UiTM Sarawak on 1 6* September 201 5 at the close of the symposium.